PERBANDINGAN METODE EKSTRAKSI MASERASI DAN REFLUKS TERHADAP KADAR FLAVONOID DAN AKTIVITAS ANTIOKSIDAN DAUN JERUJU (Acanthus ebracteatus Vahl) - Issusilaningtyas, Elisa; Azzahra, Fatimah; Nikmah Nuur Rochmah; Anita Ratna (Jurnal Komunitas Farmasi Nasional, 2023)
ABSTRACT Jeruju plant (Acanthus ebracteatus Vahl) is a type of mangrove that has the potential as a natural source of treatment. Jeruju plants contain secondary metabolite compounds including alkaloids, saponins, terpenoids, flavonoids, anthraquinones and tannins. The purpose of this study was to determine the comparison of maceration and reflux extraction methods to levels of flavonoids and antioxidant activity using the FRAP method, a plant of jeruju originating from Tegal Kamulyan, Cilacap Regency. Jeruju leaf extraction method maceration and reflux using ethanol 96% solvent. The flavonoid content of the jeruju extract was determined using a UV-VIS spectrophotometer. Antioxidant activity was measured using the FRAP method. The results of the flavonoid level determination showed that the refluxed extract contained 35,07 mg/g of flavonoids, while the macerated extract contained 27,44 mg/g of flavonoids. The calculation of the antioxidant activity of the jeruju leaf extract obtained through the reflux method was 118.57 mgAAE/g of extract with an IC50 value = 34.76 µg/mL (very strong antioxidant) and a maceration method of 111.75 mgAAE/g extract with a value of IC50 = 33,69 µ/mL (very strong antioxidant). Keywords : Jeruju, Extraction method, Flavonoids, Antioxidants